FRI0502 Risk of cancer in patients diagnosed with giant cell arteritis in western norway 1972–2012 - Brekke, L.K.; Diamantopoulos, A.P.; Fevang, B.-T.; Assmus, J.; Gjesdal, C.G. (Annals of the rheumatic diseases, 2018)
BackgroundA meta-analysis from 2014 reported a low but statistically significant increased malignancy risk among patients with giant cell arteritis (GCA), but individual epidemiological studies have shown conflicting results.1 ObjectivesTo determine the risk of cancer in GCA patients during a 41 year period.MethodsHospital-based retrospective cohort study including patients diagnosed with GCA in Bergen Health Area during 1972–2012. Patients were identified through computerised hospital records using the International Classification of Diseases (ICD)-coding system. Clinical information was extracted from patients’ medical journals. We excluded patients if data were unavailable, if the reviewing rheumatologist found GCA to be an implausible diagnosis or if the American College of Rheumatology (ACR) 1990 classification criteria for GCA were not fulfilled. Each patient was matched for age, sex, and county of residence to 3 control subjects randomly selected from the Central Population Registry of Norway. Information on the occurrence of cancer was obtained from the Cancer Registry of Norway. The cumulative incidence of malignancy in cases and controls were estimated using Kaplan-Meier plots.ResultsThe patient inclusion process and patient characteristics have been published previously.2 A total of 792 patients were included, 566 (71.5%) women (mean age 73.5 years, SD 8) and 226 (28.5%) men (mean age 72.1, SD 9). There were 2314 matched controls (excluding duplicate controls and control subjects which were also among the cases). The mean duration of follow-up for the GCA-patients was 7.2 years (SD 6.7). The mean duration of follow-up for the controls was 6.6 years (SD 6.1). The relative risk of malignancy during follow-up was higher for controls compared to cases during the majority of the observation period, but the overall difference was not statistically significant (p=0.060, figure 1). However, the subset of 528 patients (66.7%) with a positive temporal artery biopsy (TAB) had a statistically significant lower risk of malignancy compared to their matched controls (p=0.006).ConclusionsWe did not find a significant difference in the risk of malignancy in the overall GCA cohort compared to their matched controls. However, we found a statistically significant reduced risk of malignancy during follow-up for the subset of GCA-patients with a positive TAB. This is in contrast to the results of a meta-analysis which found an increased risk of malignancy in the subgroup with positive TAB. Further studies are required to determine whether this is a true difference, and what the potential causes may be.References[1] Ungprasert P, Sanguankeo A, Upala S, Knight EL. Risk of malignancy in patients with giant cell arteritis and polymyalgia rheumatica: a systematic review and meta-analysis. Semin Arthritis Rheum2014;44(3):366–70.[2] Brekke LK, Diamantopoulos AP, Fevang B-T, Aβmus J, Esperø E, Gjesdal CG. Incidence of giant cell arteritis in Western Norway 1972–2012: a retrospective cohort study. Arthritis Research & Therapy2017;19:278. doi:10.1186/s13075-017-1479-6AcknowledgementsThe study has used data from the Cancer Registry of Norway (CRN). The interpretation and reporting of these data are the sole responsibility of the authors, and no endorsement by CRN is intended nor should be inferred.Disclosure of InterestL. Brekke Grant/research support from: MSD, A. Diamantopoulos: None declared, B.-T. Fevang Consultant for: Lilly, Novartis, AbbVie, J. Assmus: None declared, C. Gjesdal: None declared